Haematopoietic stem cell transplantation for severe sickle cell disease in childhood: a single centre experience of 50 patients - Dedeken, Laurence; Lê, Phu Q.; Azzi, Nadira; Brachet, Cécile; Heijmans, Catherine; Huybrechts, Sophie; Devalck, Christine; Rozen, Laurence; Ngalula, Malou; Ferster, Alina (British journal of haematology, 2014)
Summary Despite improvements in medical management, sickle cell disease (SCD) remains associated with severe morbidity and decreased survival. Allogeneic haematopoietic stem cell transplantation (HSCT) remains the only curative approach. We report the outcome of 50 consecutive children with severe SCD that received HSCT in our unit between November 1988 and April 2013. The stem cell source was bone marrow (n = 39), cord blood (n = 3), bone marrow and cord blood (n = 7) and peripheral blood stem cells (n = 1). All patients had ≥1 severe manifestation: 37 presented with recurrent vaso‐occlusive crises/acute chest syndrome, 27 cerebral vasculopathy and 1 nephropathy. The conditioning regimen consisted of busulfan + cyclophosphamide (BuCy) before November 1991 and BuCy + rabbit antithymocyte globulin after that date. Since 1995, all patients have been treated with hydroxycarbamide (HC) prior to transplantation for a median duration of 2·7 years. Median age at transplantation and median follow‐up was 8·3 and 7·7 years, respectively. Acute graft‐versus‐host disease (GVHD) and chronic GVHD were observed in 11 and 10 patients, respectively. An excellent outcome was achieved, with 8‐year overall survival and event‐free survival (EFS) rates of 94·1% and 85·6%, respectively. Since HC introduction, no graft failure occurred and EFS reached 97·4%. Prior treatment with HC may have contributed to successful engraftment.